Swine Acute Diarrhea Syndrome Coronavirus Nucleocapsid Protein Antagonizes Interferon-β Production via Blocking the Interaction Between TRAF3 and TBK1 - Zhou, Zhihai; Sun, Yuan; Xu, Jingya; Tang, Xiaoyu; Zhou, Ling; Li, Qianniu; Lan, Tian; Ma, Jingyun (Frontiers in Immunology, 2021)
Swine acute diarrhea syndrome coronavirus (SADS-CoV), first discovered in 2017, is a porcine enteric coronavirus that can cause acute diarrhea syndrome (SADS) in piglets. Here, we studied the role of SADS-CoV nucleocapsid (N) protein in innate immunity. Our results showed that SADS-CoV N protein could inhibit type I interferon (IFN) production mediated by Sendai virus (Sev), and could block the phosphorylation and nuclear translocation of interferon regulatory factor 3 (IRF3). Simultaneously, the IFN-β promoter activity mediated by TANK binding kinase 1 (TBK1) or its upstream molecules in the RLRs signal pathway was inhibited by SADS-CoV N protein. Further investigations revealed that SADS-CoV N protein could counteract interaction between TNF receptor-associated factor 3 (TRAF3) and TBK1, which led to reduced TBK1 activation and IFN-β production. Our study is the first report of the interaction between SADS-CoV N protein and the host antiviral innate immune responses, and the mechanism utilized by SADS-CoV N protein provides a new insight of coronaviruses evading host antiviral innate immunity.